Psychological Foundations of the Cleanliness Initiative in Ahmedabad City of India (Global Journal of Human-Social Science, 2020)
Spitting on the roads of and littering around a city in India have been of concern to national leaders and civil servants since the pre-independence years. It was unsurprising, therefore, that the Prime Minister Narendra Modi launched the Swachh Bharat Abhiyan (SBA) as a nation-wide cleanliness campaign on October 2, 2014 at Rajghat, New Delhi. The cleanliness initiative by the Ahmedabad Municipal Commissioner (i) dissuades spitting on the roads and littering around the city, (ii) collects fines from those whose photos are captured by CCTV cameras, and (iii) invites active participation of all residents of Ahmedabad in the cleanliness drive. The authors present psychological foundations of this initiative, arguing that all residents ought to hold the offender and anyone else associated with such an offense as accountable. Further, they raise four new issues with the current cleanliness drive and offer suggestions for how to resolve them.
Keywords: association; commission; collective ownership; omission; norms; participation